NLRP3 Inflammasome: Checkpoint Connecting Innate and Adaptive Immunity in Autoimmune Diseases - Zhang, Yiwen; Yang, Wenlin; Li, Wangen; Zhao, Yunjuan (Frontiers in Immunology, 2021)
Autoimmune diseases are a broad spectrum of human diseases that are characterized by the breakdown of immune tolerance and the production of autoantibodies. Recently, dysfunction of innate and adaptive immunity is considered to be a key step in the initiation and maintenance of autoimmune diseases. NOD-like receptor family pyrin domain containing 3 (NLRP3) inflammasome is a multimeric protein complex, which can detect exogenous pathogen irritants and endogenous danger signals. The main function of NLRP3 inflammasome is to promote secretion of interleukin (IL)-1β and IL-18, and pyroptosis mediated by caspase-1. Served as a checkpoint in innate and adaptive immunity, aberrant activation and regulation of NLRP3 inflammasome plays an important role in the pathogenesis of autoimmune diseases. This paper reviewed the roles of NLRP3 inflammasome in autoimmune diseases, which shows NLRP3 inflammasome may be a potential target for autoimmune diseases deserved further study.